Carlos Ramón Fernández Liesa, Juan Daniel Oliva Martínez, y Oscar Pérez de la Fuente (eds.), Teoría de las obligaciones - Mercedes Galera Ruiz (Derechos y Libertades)
Este artículo reseña: Carlos Ramón FERNÁNDEZ LIESA, Juan Daniel OLIVA MARTÍNEZ, Oscar PÉREZ DE LA FUENTE (eds.), Teoría de las Obligaciones